Toxicity of the readily leachable fraction of urban PM2.5 to human lung epithelial cells: Role of soluble metals. (April 2018) - Palleschi, Simonetta; Rossi, Barbara; Armiento, Giovanna; Montereali, Maria Rita; Nardi, Elisa; Mazziotti Tagliani, Simona; Inglessis, Marco; Gianfagna, Antonio; Silvestroni, Leopoldo
Abstract: Fine airborne particulate matter (PM2.5 ) has been repeatedly associated with adverse health effects in humans. The PM2.5 soluble fraction, and soluble metals in particular, are thought to cause lung damage. Literature data, however, are not consistent and the role of leachable metals is still under debate. In this study, Winter and Summer urban PM2.5 aqueous extracts, obtained by using a bio-compatible solution and different contact times at 37 °C, were used to investigate cytotoxic effects of PM2.5 in cultured lung epithelial cells (A549) and the role played by the leachable metals Cu, Fe, Zn, Ni, Pb and Cd. Cell viability and migration, as well as intracellular glutathione, extracellular cysteine, cysteinylglycine and homocysteine concentrations, were evaluated in cells challenged with both PM2.5 extracts before and after ultrafiltration and artificial metal ion solutions mimicking the metal composition of the genuine extracts. The thiol oxidative potential was also evaluated by an abiotic test. Results demonstrate that PM2.5 bioactive components were released within minutes of PM2.5 interaction with the leaching solution. Among these are i) low MW (<3 kDa) solutes inducing oxidative stress and ii) high MW and/or water-insoluble compounds largely contributing to thiol oxidation and to increased homocysteine levels in the cell medium. Cu and/or Ni ions likely contributed to the effects of Summer PM2.5 extracts. Nonetheless, the strong bio-reactivity of Winter PM2.5 extracts could not be explained by the presence of the studied metals. A possible role for PM2.5 water-extractable organic components is discussed. Graphical abstract: Image 1 Highlights: PM2.5 low and high MW components are leached fast in a physiological solution. Fast leached compounds affect human lung alveolar cells redox status and migration. Low MW soluble compounds, including some metal ions, induce cell oxidative stress. High MW and/or insoluble compounds promote extracellular homocysteine accrual. Pb, Cd, Fe, Zn, Cu and Ni ions do not explain Winter PM2.5 soluble fraction effects.